Impact of the immuno-oncology era on cerebrovascular disease and cancer-specific mortality in older adults with advanced non-small cell lung cancer: a competing-risks cohort study - Zhou, Meijun; Huang, Yujuan; Yu, Cheng; Yao, Guang; Li, You; Xiao, Gai; Chen, Yana; Yu, Huiyun (Translational Cancer Research, 2026)
Immune checkpoint inhibitors (ICIs) have substantially improved survival for patients with advanced non-small cell lung cancer (NSCLC). However, among older adults, improved cancer survival may be accompanied by shifts in competing causes of death, including cerebrovascular disease (CVD). Population-level evidence describing how the introduction of immuno-oncology (I-O) has influenced cause-specific mortality in older patients with advanced NSCLC remains limited.